2003
DOI: 10.1136/bmj.327.7407.126
|View full text |Cite
|
Sign up to set email alerts
|

Community based retrospective study of sex in infant mortality in India

Abstract: Objective To determine whether the imbalance in the sex ratio in India can be explained by less favourable treatment of girls in infancy. Design Analysis of results of verbal autopsy reports over a five year period. Setting Community health project in urban India. Main outcome measures Deaths from all causes in infants aged less than 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 3 publications
(2 reference statements)
3
34
5
Order By: Relevance
“…The highly masculine sex ratio and excess mortality among girls and women in South Asia have been documented. [42][43][44][45][46] However, these data suggest no difference in the three selected newborn care practices according to the child's sex. Although some differences in care practices were measured, essential newborn care practices are uncommon among all socio-demographic groups.…”
Section: Breastfeedingcontrasting
confidence: 48%
“…The highly masculine sex ratio and excess mortality among girls and women in South Asia have been documented. [42][43][44][45][46] However, these data suggest no difference in the three selected newborn care practices according to the child's sex. Although some differences in care practices were measured, essential newborn care practices are uncommon among all socio-demographic groups.…”
Section: Breastfeedingcontrasting
confidence: 48%
“…This is in contrast to previous reports from other parts of the Sub-continent. 9,11 The proportional higher mortality rate in Muslims has been reported in another. study from centra!…”
Section: Discussionmentioning
confidence: 91%
“…3,4 Studies from India which examined causes of mortality have shown that in the neonatal period, the common causes of death are perinatal asphyxia, prematurity and sepsis, while in older children, infections are the commonest causes of death. [5][6][7][8][9][10][11][12] Infant mortality rates vary from state to state and over time, and are expected to change after the introduction of the IMCI. The authors therefore decided to carry out a retrospective study to determine the cause specific infant mortality during the period 1995 to 2003 in an urban slum near Vellore, which would provide both data on mortality in slum areas as well as a baseline to permit assessment of the effect of interventions.…”
mentioning
confidence: 99%
“…15 In thisa study the main causes of death in neonates were severe infection (29%) followed by LBW with prematurity (21%), Birth Asphyxia(16.6%), Congenital anomalies (12.5%) and diarrhea (4%). In post neonates, deaths were due to Pneumonia in (28.5%) followed by Diarrhoea 19% (4), Injury 4.7% (1) and congenital anomalies 4.7%(1).…”
Section: Discussionmentioning
confidence: 72%